Phytoestrogens and cancer - Mathew, BC; Reji, SD; Jamal, Al B B; Campbell, IW (Journal of Institute of Medicine Nepal, 2009)
Phytoestrogens are a group of compounds found in plants that are structurally or functionally similar to the hormone estradiol, and act as selective estrogen receptor modulators. Epidemiological studies show an inverse correlation between consumption of a high phytoestrogen-rich diet, as seen in traditional Asiatic societies, and the incidence of certain hormone- dependent cancers such, as breast and prostate cancer. Clinical studies to find a relationship between phytoestrogens, and breast and prostate cancers, have produced conflicting results. Phytoestrogens may protect against hormone-dependent cancers through their ability to lower the level of endogenous estrogens and their genotoxic metabolites, activation of estrogen receptor beta and peroxisome proliferator activated receptor gamma, inhibiting cell signaling pathways of growth factors, upregulating expression of antioxidant genes, tumor suppressor genes and immunomodulatory effects. There is little clinical evidence to suggest that phytoestrogens through their estrogenic activities will increase breast cancer risk in healthy women or worsen prognosis of breast cancer patients. Although phytoestrogens appear to hold promise as chemo preventive agents against cancer, more in-depth studies are required before definitive conclusions can be drawn. Key words: breast cancer, chemoprevention, phytoestrogen, prostate cancer, SERMs The full text of this paper is available from the Journal of Institute of Medicine website Journal of Institute of Medicine, April, 2009; 31:1 11-19